Multivariate analysis of morphometric and meristic characters of goldfish, carassius auratus, varieties. - Tajonera, Ma. Christine D.
A study using multivariate analyses of morphometric and meristic characters to attemp to determine if polymorphism is evident in different populations of goldfish (Carassius auratus) is described. The morphological relationships are investigated between thirty (30) samples of Black Moor, Calico and Fantail varieties from one collecting site. Data were obtained from five (5) morphometric and five (5) meristic characters. Analyzes of both morphometric and meristic characters provided no evidence of significant differences among the populations studied. Although distinct variations may be seen in the varieties' color and shape. The results suggest that goldfish varieties could not be separated using morphometric and meristic characters as, body depth, standard lenght, interorbital width, diameter of the eye, caudal fin rays, anal fin rays, pelvic fin rays and pectoral fin rays. On the other hand, lenght of the heads and the dorsal fin rays showed greater variations. The paper concludes with suggestions for further studies using biochemical tests such as electrophoretic analyses of proteins and DNA to distinctly separate the goldfish varieties.